The Reception of Satellite Broadcast in Public Administration Teaching at the University of South Africa - Wessels, Rochelle (Mediterranean Journal of Social Sciences, 2012)
The University of South Africa (UNISA) is an open learning distance education institutionwith approximately 220 000 registered students for 2012. Open distance learning (ODL)aims to bridge the time, geographical, and educational distances between the students andthe institution by removing barriers to access learning. UNISA currently uses non printinteraction, such as face-to-face contact sessions, to promote student success andmotivation. Interaction is a crucial element of the UNISA student support conceptualframework, as students engage with their material, their lecturers and with their fellowstudents to attain success in their studies. UNISA students do not attend regular classes.The average current UNISA student encounters difficulty in mastering the content ofmaterial in an isolated learning environment. This led to the need to consider alternativemethods of academic support. Satellite broadcast is a live or pre-recorded presentation oflectures or tutorials to students via a television screen at remote venues across the country.The use of satellite broadcast is especially relevant to students in South Africa studying atUNISA, as a large number of students live in rural and remote areas, and do not havecontact with their lecturers or their peers. The researcher has been using this method ofteaching for the past two years and has found that this teaching method assists thestudents with their learning processes. The researcher conducted a pilot exploratory studyon a small group of students who represent the Public Administration diploma studentswho attended the satellite broadcast classes. All students who attended the satellitebroadcast class were requested to complete the evaluation questionnaire. The perceptionsand experiences of the students were ascertained through the use of the evaluationquestionnaire. With the questionnaire, the researcher wanted to ascertain the perceptionsand experiences of the students of the satellite broadcast class. The researcher found thatthe students experienced this mode of teaching as generally beneficial to their overalllearning experience. This study will serve as a premise for further investigation on theeffectiveness of the ODL method of teaching Public Administration subjects so as toimprove the throughput of the students.